MUSTANG 0 A low-cost technology demonstration nanosatellite. Summary of the Group Design Project MSc in Astronautics and Space Engineering 2004/05 Cranfield University - Hobbs, Stephen (Cranfield University, 2005)
Students of the MSc course in Astronautics and Space Engineering 2004/05 at Cranfield University took Mustang 0 as their group project. This report summarises their findings. Mustang is a partnership of several groups interested in technology for small spacecraft: Mustang 0 is intended to be a simple spacecraft suitable for technology demonstration (especially highly miniaturised systems based on MEMS or microsystem technology (MST)). A parallel student project took place in the School of Industrial and Manufacturing Science at Cranfield University to investigate MST available from non-space sectors and the qualification process for space hardware. Design studies have been performed for all the spacecraft sub-systems and build on previous work by Mustang partners. The spacecraft designed has a mass of just less than 10 kg, a lifetime of 1 year, is 3-axis controlled, and could be launched to either GTO or LEO. New areas studied this year include software design and operations, and some hardware (the main structure) has been manufactured. The project conclusion is that a low-cost (< £ 100k for a flight-ready space- craft) technology demonstration mission is possible. The Mustang 0 study identifies no fundamental problems, although a significant amount of work remains. Many sub-systems now require prototyping to validate and develop the proposed designs